OVERVIEW OF THE METHODS USED IN THE ELECTRONIC DICTIONARY OF IT TERMS AND PHRASES - Rakhimova, Д.Р.; Buribayev, Б.Б.; Turarbek, Ә.Т.; Kenesova, Н.А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
The purpose of the study is to review the methods used in the electronic dictionary of IT terms and phrases, and to choose a method that provides translation while preserving the meaning of the word. The article discusses the methods used in machine translation in electronic dictionaries: the method of literal translation, the method of indirect translation, the method of reverse translation – of these, literal translation and indirect translation consist of several internal methods. It can be seen from these methods that only one terminological phrase can receive a multi-valued translation using various methods. The scientific novelty of the work consists in determining the methods used in the electronic dictionary of terms and phrases in the field of modern dynamically developing information technologies. As a result, it was found that the methods of literal translation and reverse translation are methods that preserve the original meaning and meaning of translations of terms and phrases used in information technology.